ID 51 – Correlation between abnormal brain excitability, anger management and anxiety in migraine children. Issue 3 (March 2016) - Pro, S.; Iacovelli, E.; Tarantino, S.; Vollono, C.; Capuano, A.; Vigevano, F.; Valeriani, M.
Abstract : Objective: To analyze the possible correlation between abnormal brain excitability and psychologic factors in migraine children. Methods: We studied 12 migraine children. Auditory event-related potentials (ERPs) were recorded in three successive blocks to test habituation. Psychologic profile was assessed by Picture Frustration Study test for anger management (PFS) and Psychiatric scales for self-administraion for youths and adolescents (SAFA-A scale for anxiety). Results: In migraineurs, all the ERP components (N1, P2, and P300) showed a reduced habituation, as compared to healthy children. In both the second and third blocks, a significant correlation between P300 deficit habituation and SAFA-A (social anxiety subscale) was found. Moreover, the P300 habituation was also correlated with PFS-I (intraggressive anger) in the second block and with the total SAFA-A score in the third block. Conclusions: To our knowledge, this is the first study showing a correlation between abnormal brain excitability, intraggressive anger and anxiety, suggesting a possible role of the latters in producing the migraine phenotype in children. Key message: Neurophysiological and psychologic elements are strictly related in the pathophysiology of pediatric migraine.